2-Norm-Based Iterative Design of Filterbank Transceivers: A Control Perspective. (13th March 2008) - Shi, Yang; Chen, Tongwen
Abstract : This paper considers design of filterbank-based transceivers. A composite error criterion is proposed to capture all the three traditional distortions. Incorporating noise attenuation and filter bandlimiting properties into this error criterion, an optimal design procedure is developed and applied to a transceiver design example, yielding an FIR transceiver that has good frequency-selective properties and is close to perfect reconstruction. As a least-squares solution is given in closed form in each iteration, the algorithm is easy to implement.